2018
DOI: 10.1016/j.carpath.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound induces coronary perivascular fibrosis in rats

Abstract: Background: Chronic exposure to industrial noise is known to affect biological systems, namely, by inducing fibrosis in the absence of inflammatory cells. In rat hearts exposed to this environmental hazard, we have previously found myocardial and perivascular fibrosis. The acoustic spectrum of industrial environments is particularly rich in high-intensity infrasound (b20 Hz), whose effects on the heart are unknown. We evaluated the morphological changes induced by IFS in rat coronaries in the presence and abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…The present study evaluated two specific features of myocardial remodeling in rat heart, interstitial fibrosis and Cx43 modifications, as a consequence of exposure to IFS (120 dB, < 20 Hz) and validated our initial hypothesis that exposure to different periods of high-intensity IFS can lead to structural atrial remodeling. These results are consistent with those of past investigations from our group, also in Wistar rats (Oliveira et al, 2005;Oliveira et al, 2012;Oliveira et al, 2013;Antunes et al, 2013a;Lousinha et al, 2015;Antunes et al, 2013b;Antunes et al, 2013c;Antunes et al, 2013d;Lousinha et al, 2018), confirming the abnormal proliferation of connective tissue as the main morphological change induced by LFN exposure. In our study, Cx43 also appears to undergo age-dependent loss, as lower concentrations were found among ≥22 weeks-old controls compared to younger rats (16 weeks-old), a result that comes in agreement with previously reported data from Watanabe et al (Watanabe et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study evaluated two specific features of myocardial remodeling in rat heart, interstitial fibrosis and Cx43 modifications, as a consequence of exposure to IFS (120 dB, < 20 Hz) and validated our initial hypothesis that exposure to different periods of high-intensity IFS can lead to structural atrial remodeling. These results are consistent with those of past investigations from our group, also in Wistar rats (Oliveira et al, 2005;Oliveira et al, 2012;Oliveira et al, 2013;Antunes et al, 2013a;Lousinha et al, 2015;Antunes et al, 2013b;Antunes et al, 2013c;Antunes et al, 2013d;Lousinha et al, 2018), confirming the abnormal proliferation of connective tissue as the main morphological change induced by LFN exposure. In our study, Cx43 also appears to undergo age-dependent loss, as lower concentrations were found among ≥22 weeks-old controls compared to younger rats (16 weeks-old), a result that comes in agreement with previously reported data from Watanabe et al (Watanabe et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…In the cardiovascular system of rodents, we reported the development of perivascular fibrosis around the coronary arteries of rats exposed to industrial noise (Antunes et al, 2013a;Lousinha et al, 2015) and documented a significant fibrotic development in ventricular myocardium among rats submitted to LFN (Antunes et al, 2013b;Antunes et al, 2013c), together with a possible ventricular gap junction remodeling (Antunes et al, 2013d). We also found that IFS exposure induces coronary perivascular fibrosis (Lousinha et al, 2018).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…No changes were observed in the lumen-to-wall ratio. With dexamethasone treatment and exposure, no differences were observed in the wall-to-perivascular-space ratio, as compared to controls, suggesting an underlying inflammatory mechanism [46].…”
Section: Heart Cells and Tissuesmentioning
confidence: 79%
“…There is evidence from high-intensity infrasound exposure studies in laboratory animals that chronic exposure results in proliferation of the connective tissue matrix and collagen fibers in animals; this fibrotic response has been documented in several organs, such as the heart, lung and glands of rats chronically exposed to industrial-type noise [ 27 , 28 , 29 , 30 ]. Oliveira et al.…”
Section: Discussionmentioning
confidence: 99%